Analisis Kinerja Pelayanan Transportasi Umum Suroboyo Bus dan Trans Semanggi di Dinas Perhubungan Kota Surabaya - Hanifa Putri Ambarini; Eva Hany Fanida; Meirinawati Meirinawati; Fitrotun Niswah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
In Surabaya City, the City Government through the Transportation Agency developed the Suroboyo Bus and Trans Semanggi programs to address traffic congestion, limited public transportation, and the need for safe, comfortable, and environmentally friendly transportation. However, complaints are still found regarding limited facilities, irregular schedules, and suboptimal communication services, so that service performance evaluation is needed from the user's perspective. This study aims to analyze the performance of Suroboyo Bus and Trans Semanggi public transportation services at the Surabaya City Transportation Agency using five public service performance indicators according to Dwiyanto et al. (2021), namely productivity, service quality, responsiveness, responsibility, and accountability. The approach used is quantitative with the Importance Performance Analysis (IPA) method. The results of the study show an average expectation score (importance) of 4.18 and a reality score (performance) of 3.86 with an overall gap of -0.32, which means that the performance of Suroboyo Bus and Trans Semanggi services still does not meet public expectations. Through the IPA mapping, three attributes are in Quadrant I (high priority): the friendly and professional attitude of staff, the adequacy of on-board facilities, and the transparency of official information regarding schedules and service changes. A total of 13 attributes are in Quadrant II (maintained), 13 attributes in Quadrant III (low priority), and one attribute in Quadrant IV (excessive).